2002
DOI: 10.1521/jaap.30.1.71.21988
|View full text |Cite
|
Sign up to set email alerts
|

From Victim to Heroine: Children's Stories Revisited

Abstract: The need to escape reality and the taste for adventure with the unknown fills a universal need for both adults and children. Fairy tales have a powerful grip on the imagination because they are homespun versions of myths and have passionate intensity without epic grandeur. The happy ending of fairy tales reflects gender stereotyping because the heroine usually does very little except sit, wish, and wait for marriage. She has no control over her destiny and no active involvement in selecting or planning her fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2009
2009
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
2
0
5
Order By: Relevance
“…In addition, a rather unexpected result of this research was that no differences were found concerning the preferences of children in relation to gender, something that probably reflects a new trend, which is also obvious in modern children's literature. Modern stories do not use as much stereotyped presentations as classic fairy tales do (Turkel 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a rather unexpected result of this research was that no differences were found concerning the preferences of children in relation to gender, something that probably reflects a new trend, which is also obvious in modern children's literature. Modern stories do not use as much stereotyped presentations as classic fairy tales do (Turkel 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Os contos de fadas distinguem-se das demais histórias infantis por características como o uso de magia e encantamentos, um núcleo problemático existencial no qual o herói ou a heroína busca sua realização pessoal e, finalmente, a existência de obstáculos a serem enfrentados pelos heróis (Caldin, 2002;Oliveira, 2001;Radino, 2003;Turkel, 2002). Para Bettelheim (1980), é característica desses contos a presença de um dilema existencial de forma sucinta e categórica.…”
Section: Na Mágica Viagem Dos Contos De Fadas Um Pouco De Históriaunclassified
“…Na clínica psicanalítica contemporânea, faz-se corriqueiro o uso de histórias infantis com crianças e adultos para diagnóstico e tratamento (Bernstein, 1999;Bettelheim, 1980;Brandt, 1983;Bruder, 2004;Caillé & Rey, 1990;Castello, 1999;Catheline-Antipoff & Soulayrol, 1994;Chauí, 1984;Davies, 1988;Dieckmann, 1997;Ellis, 1990;Erle, 1999;Fagulha, 1999;Ferreira, 1991;Ferro, 1995;Garcia & Garcia, 2005;Goldmann, 2001;Gutfreind, 2000Gutfreind, , 2002Gutfreind, , 2003Hisada, 1998;Ishikawa et al, 1990;Luz & Zanetti, 2003;Machado, 1988;Roberge, 2002;Robinson, 1986;Safra, 2005;Schmid et al, 2002;Silva & Fachin, 2002;Souyouldzoglou, Anasiassia, Coulacoglou, & Gardiner, 1999;Sussenbacher, 1982;Stube, 2001;Turkel, 2002;Tychey, 1993;Zago, 1998).…”
Section: Os Contos De Fadas Como Dispositivo De Intervenção Na Práticmentioning
confidence: 99%
“…um núcleo problemático existencial no qual o herói ou a heroína busca sua realização pessoal e, finalmente, (3.) a existência de obstáculos a serem enfrentados pelos heróis (TURKEL 2002;cf. CALDIN, 2002).…”
Section: Uma Breve Descrição Do Contexto E Uso Das Histórias Infantisunclassified
“…Constata-se, portanto, que a literatura oferece subsídios ao resgate da veiculação secular dos Contos de Fadas pelas mais diversificadas culturas e gerações, encantando adultos e, sobretudo crianças, inclusive na atualidade -muito embora tenha havido mudanças nas últimas 3 Outros autores que corroboram uma visão mais abrangente das histórias infantis: (CHAUÍ, 1984;ROBINSON, 1986;CAILLÉ;REY, 1988;DAVIES, 1988;MACHADO, 1988;ELLIS, 1990;ISHIKAWA, et al, 1990;FERREIRA, 1991;TYCHEY, 1993;FERRO, 1995;HISADA, 1998;ZAGO, 1998;FAGULHA, 1999;ERLE, 1999;BERNSTEIN, 1999;GOLDMANN, 2001;SCHMID, et al, 2002;SILVA;FACHIN, 2002;TURKEL, 2002;GUTFREIND, 2002GUTFREIND, , 2003LUZ;ZANETTI, 2003;GARCIA;GARCIA, 2005;SAFRA, 2005;SCHNEIDER;TOROSSIAN, 2009).…”
Section: Uma Breve Descrição Do Contexto E Uso Das Histórias Infantisunclassified